2015
DOI: 10.1097/nmd.0000000000000321
|View full text |Cite
|
Sign up to set email alerts
|

Are Suicide Attempters Wired Differently?

Abstract: Limited research exists on internal risk processes in suicide attempters and factors that distinguish them from nonsuicidal depressive individuals. In this qualitative study, we investigated Plans, motives, and underlying self-regulatory processes of the two groups and conducted a comparative analysis. We analyzed narrative interviews of 17 suicide attempters and intake interviews of 17 nonsuicidal depressive patients using Plan Analysis. Then, we developed a prototypical Plan structure for both groups. Suicid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Although the exact mechanism that links suicide and chronic stress is not fully understood, stress-related alterations in cell structure have been documented in suicide attempters {41}. Chronic dysregulation of the habenula circuit may lead to long-term alterations of dopamine, serotonin, and norepinephrine release that impact behavioral functioning, particularly the learning of maladaptive coping strategies related to suicide-related behaviors {42}. Interestingly, the parahippocampal gyrus has been linked to suicidality: in an fMRI experiment using a delay discount task, suicidal patients showed longer reward delays were associated with diminished parahippocampal response {43}.…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact mechanism that links suicide and chronic stress is not fully understood, stress-related alterations in cell structure have been documented in suicide attempters {41}. Chronic dysregulation of the habenula circuit may lead to long-term alterations of dopamine, serotonin, and norepinephrine release that impact behavioral functioning, particularly the learning of maladaptive coping strategies related to suicide-related behaviors {42}. Interestingly, the parahippocampal gyrus has been linked to suicidality: in an fMRI experiment using a delay discount task, suicidal patients showed longer reward delays were associated with diminished parahippocampal response {43}.…”
Section: Discussionmentioning
confidence: 99%
“…A number of empirical studies have investigated Plan structures and their clinical application in mental disorders such as borderline personality disorder, depression, and bipolar disorder (Berthoud, Kramer, de Roten, Despland, & Caspar, 2013;Brüdern et al, 2015;Kramer, Berger, & Caspar, 2009;Kramer et al, 2011Kramer et al, , 2014. For instance, in a study with 85 patients with borderline personality disorder, Kramer et al (2014) reported an additional reduction of general problems (e.g., social problems) and an increase in the therapeutic alliance in a condition with a manualbased short variant of the general psychiatric management treatment amended with motive-oriented therapy relationship building based on Plan analysis, compared with general psychiatric management alone.…”
mentioning
confidence: 99%